2022
DOI: 10.1186/s12872-022-02611-y
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Italian children and adolescents with congenital heart diseases

Abstract: Background Congenital heart disease (CHD) is the most common congenital anomaly at birth, affecting approximately 1% of live births. In recent decades great medical and surgical advances have significantly increased life expectancy, shifting healthcare professionals' and researchers’ interests in patients' Quality of Life (QoL). The main aims of our study were to evaluate generic and condition-specific QoL in a group of Italian children and adolescents with CHD and their parents and examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(95 reference statements)
1
6
0
1
Order By: Relevance
“…The study found a signi cant difference between CCHD and healthy children in terms of a child while receiving treatment. In this respect, Amodeo et al 2022 reported the same ndings in Italy 45 .…”
Section: Discussionmentioning
confidence: 70%
“…The study found a signi cant difference between CCHD and healthy children in terms of a child while receiving treatment. In this respect, Amodeo et al 2022 reported the same ndings in Italy 45 .…”
Section: Discussionmentioning
confidence: 70%
“…The cardiac-speci c module of the HRQoL questionnaire investigates aspects of the child's health related to their CHD, such as the presence of cardiac symptoms, treatment adherence, and anxiety about treatment (Grimaldi . In their previous study, Amodeo et al (2022) found signi cant differences among six categories of young patients with CHD (i.e., aortopathies (Ao), patients with aortic disease from the aortic valvular lesion to the aortic arch anomalies; tetralogy of Fallot (ToF); univentricular heart (UVH), patients treated with Glenn or Fontan palliation according to the UVH physiology they had; right ventricular-pulmonary artery conduit (RV-PA conduit); transposition to the great arteries (TGA), and other congenital heart disease (oCHD)), which included a miscellaneous of diseases not considered above and the quality of life perceived by patients. Young patients with UVH showed the worst HRQoL levels referred to the cardiac-speci c module overall.…”
Section: Chd Young Patients: the Health-related Quality Of Lifementioning
confidence: 89%
“…Several topics were discussed based on the review of 11 articles, including 5 articles discussing the relationship between quality of life in children with Congenital Heart Disease and healthy or normal children [8,10,12,13,15], 2 articles discussing quality of life in children with CHD according to patient age group [6,11], 3 articles discussing the relationship between quality of life for children with CHD and the type of CHD severity [5,9,14], and 1 article about the relationship between perceived quality of life between children with CHD and caregivers [7].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study by Angeles Fuertes et al in particular are important for clinical practice and future research because they highlight the importance of quality of life assessment in routine clinical practice. This is particularly important for patients aged 5 to 7 years, during the transition from home to primary school and adolescents to support the development of body image and adherence to medical processes [9].…”
Section: Discussionmentioning
confidence: 99%